Diversification of rice-wheat cropping systems for enhancing farmers’ profit in Indo-Gangetic plains - Burman, Rajarshi Roy; Singh, Rahul; Sharma, Shailendra; Rao, D.U. M.; Sharma, J. P.; Singh, A. K.; Singh, S. K.; Rohilla, P. P. (Indian Farming, 2019)
Rice-wheat cropping system has been the only source of livelihood for large sections of farmers in the Indo-Gangetic plains. This cropping system has shown source vulnerabilities to both climate change, and food and livelihood security. Demonstrations conducted under Farmer FIRST Programme in Palwal district of Haryana showed that diversification of rice-wheat cropping system in the Indo-Gangetic plains by adopting short duration basmati, wheat and summer mungbean can enhance farm profits besides conserving natural resources. Summer mungbean crop can be raised for grain and green manure for enriching soil health. The per day productivity of food grains has increased from 61.36 to 85.21 kg after introduction of mungbean as summer crop in the alternative cropping system.